2012
DOI: 10.1128/jvi.01034-12
|View full text |Cite
|
Sign up to set email alerts
|

The Pre-NH 2 -Terminal Domain of the Herpes Simplex Virus 1 DNA Polymerase Catalytic Subunit Is Required for Efficient Viral Replication

Abstract: The catalytic subunit of herpes simplex virus 1 DNA polymerase (HSV-1 Pol) has been extensively studied; however, its full complement of functional domains has yet to be characterized. A crystal structure has revealed a previously uncharacterized pre-NH 2 -terminal domain (residues 1 to 140) within HSV-1 Pol. Due to the conservation of the pre-NH 2 -terminal domain within the herpesvirus Pol family and its location in the crystal structure, we hypothesized that this domain provides an important function during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 45 publications
2
29
1
Order By: Relevance
“…Interestingly, the HSV-1 DNApol has an extra domain, the pre-NH 2 -terminal domain, according to the three dimensional structure published by Liu et al (32). This domain is required for efficient viral replication as well as for establishment of latency (as observed experimentally in mice) (33,34). In EBV DNApol, the pre-NH 2 -terminal domain is also important for lytic genome replication (35).…”
Section: Structural Features Of Dna Polymerase B Familymentioning
confidence: 99%
“…Interestingly, the HSV-1 DNApol has an extra domain, the pre-NH 2 -terminal domain, according to the three dimensional structure published by Liu et al (32). This domain is required for efficient viral replication as well as for establishment of latency (as observed experimentally in mice) (33,34). In EBV DNApol, the pre-NH 2 -terminal domain is also important for lytic genome replication (35).…”
Section: Structural Features Of Dna Polymerase B Familymentioning
confidence: 99%
“…The pre-N terminal domain also contains the FYNPYL motif specific to herpesviridae family polymerases (Appendix Figure A1) [9]. It has recently been shown that this motif is required for efficient replication of viral DNA synthesis in vivo ; a mutant polymerase lacking the FYNPYL motif showed a substantial reduction in viral DNA synthesis [34]. However, the purified FYNPYL deletion mutant showed no reduction in polymerase activity, suggesting that this motif may have a function in the formation of the viral DNA replisome.…”
Section: Subdomains Of B Family Polymerasementioning
confidence: 99%
“…To test whether the RNase H activity of HSV-1 Pol requires an active 3=-to-5= exonuclease catalytic site, we analyzed the in vitro activities of purified WT Pol and the previously characterized exonuclease-deficient single mutant, D368A Pol (17,18). We expressed 6ϫHis-tagged full-length WT Pol and 6ϫHis-tagged D368A Pol separately using baculovirus expression (22) and purified these enzymes for in vitro characterization. Next, we assessed the 5=-to-3= polymerization function of both enzymes by testing the ability of these Pols and control enzymes to extend a hairpin template (S1) with a 5= overhang and a 5= fluorescent label ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Protein expression and purification. 6ϫHis-tagged full-length WT HSV Pol and a previously characterized 3=-to-5= exonuclease-deficient mutant, D368A Pol (17,18), were cloned into the pFastBac HTC vector and expressed in a baculovirus system as previously described (22) and then purified as follows. Cells were harvested at 65 h postinfection and centrifuged at 2,800 ϫ g for 30 min.…”
Section: Methodsmentioning
confidence: 99%